Family as a Social Influence Manager in Determining the Lifestyle of Students in the Campus Environment - Maunah, Binti; Komsiyah, Indah (Didaktika Religia, 2023)
This article aims to explore the role of the family in the realization of student lifestyle on the campuses of UIN Sunan Kalijaga Yogyakarta, UIN Sayyid Ali Rahmatullah Tulungagung, and IAIN Kediri. Qualitative field research with a multi-case study approach was taken as the methodological perspective. In-depth interviews, participatory observation, and documentation were conducted to collect data. This article concludes that family plays a significant role in shaping the lifestyle patterns of students on the three campuses. The family as a social influence manager contributes greatly to determining the lifestyle of students when they are in the campus environment. The values, habits, and beliefs taught by the family since childhood greatly influence the lifestyle of students. Students’ lifestyles are also indicated to follow the habits of their immediate environment. Several obstacles in regulating student lifestyles were found. The campus has implemented some effective solutions so that student lifestyles remain by applicable ethics.